2023
DOI: 10.1002/jcv2.12127
|View full text |Cite
|
Sign up to set email alerts
|

IQ trajectories in autistic children through preadolescence

Abstract: Background We extended our study of trajectories of intellectual development of autistic individuals in early (mean age 3 years; T1), and middle childhood (mean age 5 years, 7 months; T2) into later middle childhood/preadolescence (mean age 11 years, 6 months; T3) in the longitudinal Autism Phenome Project cohort. Participants included 373 autistic children (115 females). Methods Multivariate latent class growth analysis was used to identify distinct IQ trajectory subgroups. Baseline and developmental course g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…They found that PIQ and VIQ showed comparable development for almost 75% of the participating children, while approximately one‐quarter showed decline. In a follow‐up study that tested intellectual development in autism from early childhood through preadolescence, Solomon et al (2023) found that a considerable number of the autistic participants (almost 40%) improved in IQ for at least 1 standard deviation from early childhood through age 12.…”
Section: Introductionmentioning
confidence: 99%
“…They found that PIQ and VIQ showed comparable development for almost 75% of the participating children, while approximately one‐quarter showed decline. In a follow‐up study that tested intellectual development in autism from early childhood through preadolescence, Solomon et al (2023) found that a considerable number of the autistic participants (almost 40%) improved in IQ for at least 1 standard deviation from early childhood through age 12.…”
Section: Introductionmentioning
confidence: 99%
“…When developmental trajectories are examined, this subgroup of those with co‐occurring delays and/or limited verbal communication tends to have a stable or worsening trajectory across time. (Georgiades et al, 2013; Pickles et al, 2020; Solomon et al, 2023; Szatmari et al, 2015; Waizbard‐Bartov et al, 2022). Some groups have described samples of exclusively minimally verbal autistic individuals within a single domain (Bal et al, 2016; Chang et al, 2018; Frost et al, 2017; Harrop et al, 2021).…”
Section: Introductionmentioning
confidence: 99%